2007
DOI: 10.1016/j.ydbio.2007.07.041
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage link protein 1 (Crtl1), an extracellular matrix component playing an important role in heart development

Abstract: To expand our insight into cardiac development, a comparative DNA microarray analysis was performed using tissues from the atrioventricular junction (AVJ) and ventricular chambers of mouse hearts at embryonic day (ED) 10.5-11.0. This comparison revealed differential expression of approximately 200 genes, including cartilage link protein 1 (Crtl1). Crtl1 stabilizes the interaction between hyaluronan (HA) and versican, two extracellular matrix components essential for cardiac development. Immunohistochemical stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
96
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 77 publications
(102 citation statements)
references
References 64 publications
(98 reference statements)
5
96
0
Order By: Relevance
“…For example, individuals with Down syndrome (Trisomy 21) have remarkably similar types of AVSD that are associated with defects in DMP expansion (Blom et al, 2003). AVSD is also observed in the Ts16 Down syndrome mouse model, in which the DMP is deficient (Webb et al, 1999;Snarr et al, 2007). Here, we demonstrate that AVSD can be the direct result of defective DMP development in mice.…”
Section: Mef2c-ahf-cre; Smosupporting
confidence: 52%
See 1 more Smart Citation
“…For example, individuals with Down syndrome (Trisomy 21) have remarkably similar types of AVSD that are associated with defects in DMP expansion (Blom et al, 2003). AVSD is also observed in the Ts16 Down syndrome mouse model, in which the DMP is deficient (Webb et al, 1999;Snarr et al, 2007). Here, we demonstrate that AVSD can be the direct result of defective DMP development in mice.…”
Section: Mef2c-ahf-cre; Smosupporting
confidence: 52%
“…However, new findings suggest that AVSDs seen in perinatal humans are more complex in their origins. Previous work has demonstrated that deficient DMP development occurs in mouse (Webb et al, 1999;Snarr et al, 2007b;Wirrig et al, 2007) and human (Blom et al, 2003) fetuses with AVSD. As such individuals exhibit malformations in other septal structures, the specific role of DMP defects in generating these malformations has been unclear.…”
Section: Discussionmentioning
confidence: 99%
“…11 Thus, as we continued to gain more insight into the matter we opted to use this terminology. 7,12 We acknowledge, however, that "atrial spine", "vestibular spine", and "spina vestibuli" are also commonly, and legitimately, used in other articles to describe this mesenchymal population.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to tissue colocalization, studies using recombinant proteins have demonstrated the molecular interactions of Crtl1/ Hapln1 in the formation of other proteoglycan aggregates, versican and neurocan (Matsumoto et al, 2003;Shi et al, 2004;Rauch et al, 2004). Although expression of Crtl1/ Hapln1 was reported in several developing tissues (Binette et al, 1994;Deak et al, 1999;Wirrig et al, 2007, Shibata et al, 2003, Colas and Schoenwolf, 2003, a detailed embryonic expression analysis is required for understanding its biological roles. Furthermore, cross-species comparison of Crtl1/Halpn1 would shed light on the evolutionary conservation and/or diversity of the structure and function, though such study has not yet been performed.…”
Section: Introductionmentioning
confidence: 99%